Effect of Cationic Interface Defects on Band Alignment and Contact Resistance in Metal/Oxide Heterojunctions. (18th November 2019) - Andrä, Michael; Funck, Carsten; Raab, Nicolas; Rose, Marc‐André; Vorokhta, Mykhailo; Dvorˇák, Filip; Šmíd, Brˇetislav; Matolín, Vladimír; Mueller, David N.; Dittmann, Regina; Waser, Rainer; Menzel, Stephan; et al.
Abstract: Heterojunctions between high‐work‐function metals and metal oxides typically lead to Schottky‐type transport barriers resulting from charge transfer between the neighboring materials. These yield versatile electronic functionality exploited for current rectification, memristive behavior, or photocatalysis. Height, width, and shape of the interfacial transport barrier are strongly affected by charge screening via ionic defects, which are often extremely difficult to probe. The ionic nature of a variable contact resistance in heterojunctions between Nb‐doped SrTiO3 (Nb:SrTiO3 ) and platinum is explored. A control of cationic vacancy defects at the interface is achieved by different annealing procedures in oxidizing and reducing conditions before establishing Pt/Nb:SrTiO3 heterojunctions. Detailed analysis of electronic transport across the heterojunctions reveal significantly varied transport barriers resulting from the cationic defect structure at the interface. These findings are supported by conductive‐tip atomic force microscopy and in situ photoemission spectroscopy showing diminished conductivity of the Nb:SrTiO3 surface and the formation of an insulating surface skin layer after oxygenation. At high doping level, oxygen stoichiometry cannot explain the observed behavior. The increased transport barrier height is therefore linked to strontium vacancy defects. The tailored cation disorder yields access to the ionic control of electronic transport in functional oxide heterojunctions. Abstract : Ionic defects play an essential role in the screening of interfacial charges in complex oxides. The influence of cation vacancy defects on the charge screening in Pt/Nb:SrTiO3 heterjunctions serving as model systems for metal/metal‐oxide interface devices is demonstrated. The ability to tune the concentration of cationic defects at the interface allows to tailor the transport barrier at the interface.